2016
DOI: 10.1016/j.jhin.2015.08.027
|View full text |Cite
|
Sign up to set email alerts
|

Transmission of SARS and MERS coronaviruses and influenza virus in healthcare settings: the possible role of dry surface contamination

Abstract: Viruses with pandemic potential including H1N1, H5N1, and H5N7 influenza viruses, and severe acute respiratory syndrome (SARS)/Middle East respiratory syndrome (MERS) coronaviruses (CoV) have emerged in recent years. SARS-CoV, MERS-CoV, and influenza virus can survive on surfaces for extended periods, sometimes up to months. Factors influencing the survival of these viruses on surfaces include: strain variation, titre, surface type, suspending medium, mode of deposition, temperature and relative humidity, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
643
2
22

Year Published

2017
2017
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 729 publications
(681 citation statements)
references
References 105 publications
14
643
2
22
Order By: Relevance
“…It is therefore of utmost importance to prevent any further spread in the public and healthcare settings. Transmission of coronaviruses from contaminated dry surfaces has been postulated including self-inoculation of mucous membranes of the nose, eyes or mouth [4,5], emphasizing the importance of a detailed understanding of coronavirus persistence on inanimate surfaces [6]. Various types of biocidal agents such as hydrogen peroxide, alcohols, sodium hypochlorite or benzalkonium chloride are used worldwide for disinfection, mainly in healthcare settings [7].…”
Section: Introductionmentioning
confidence: 99%
“…It is therefore of utmost importance to prevent any further spread in the public and healthcare settings. Transmission of coronaviruses from contaminated dry surfaces has been postulated including self-inoculation of mucous membranes of the nose, eyes or mouth [4,5], emphasizing the importance of a detailed understanding of coronavirus persistence on inanimate surfaces [6]. Various types of biocidal agents such as hydrogen peroxide, alcohols, sodium hypochlorite or benzalkonium chloride are used worldwide for disinfection, mainly in healthcare settings [7].…”
Section: Introductionmentioning
confidence: 99%
“…Multiple studies on CoVs other than MERS-CoV have demonstrated that these viruses can remain viable for days to weeks on environmental surfaces. 88,89 Survival is enhanced at low temperatures (ie, 4°C vs 20°C). 89…”
Section: Environmental Contamination and Survivalmentioning
confidence: 99%
“…In this regard, studies suggest that surfaces and suspensions can carry HCoVs, increasing the risk of contact transmission that could lead to hospital acquired HCoVs infections [4,5]. Otter et al found that other coronaviruses (SARS-CoV, MERS-CoV) can be found on plastic, metal and cloths for up to 6 days [6]. Thus, monitoring environmental contamination of SARS-CoV-2 can support investigation of the current outbreak and benefit the management of COVID-19 infection.…”
mentioning
confidence: 99%